Da Primavera Árabe à tempestade decisiva: os processos que levaram ao conflito no Iêmen (2011-2015) - Oliveira, Verônica D'Angelo de (2022)
The present work aims to analyze the processes that led to the current conflict in Yemen, between the departure of then President Ali Abdullah Saleh in 2011 after the manifestations of the so-called Arab Spring until the beginning of Operation Decisive Storm led by Saudi Arabia in March 2015. Our main argument is that disputes between domestic elites and their articulations with foreign elites made it possible for the then president to leave and created conditions for military intervention in the country